2019
DOI: 10.1111/jce.14185
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of arrhythmia endpoints in randomized controlled trials of transendocardial stem cell injections for chronic ischemic heart disease

Abstract: Introduction The electrophysiologic impact of cell‐based therapy on the injured myocardium remains highly controversial. We aimed to perform a meta‐analysis of studies comparing arrhythmia burden following transendocardial stem cell therapy vs placebo in patients with chronic ischemic heart disease (CIHD). Methods and Results PubMed, Embase, and Cochrane Central Register of Controlled Trials were searched. No restriction of stem cell type was specified. The outcomes included sustained supraventricular or ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…After removing the duplicates, we started our selection and evaluated 184 papers, with 52 assessed as full text. As reported in the PRISMA flow-chart (Figure 1), we identified 11 meta-analyses as eligible, with 34 outcomes (Fan et al, 2019;Fernandes et al, 2019;Jayaraj et al, 2019;Jeong et al, 2018;Jiang et al, 2016;Jones et al, 2019;Kuswardhani and Soejitno, 2011;Liu et al, 2015;Marquis-Gravel et al, 2014;Sun et al, 2015;Velagapudi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After removing the duplicates, we started our selection and evaluated 184 papers, with 52 assessed as full text. As reported in the PRISMA flow-chart (Figure 1), we identified 11 meta-analyses as eligible, with 34 outcomes (Fan et al, 2019;Fernandes et al, 2019;Jayaraj et al, 2019;Jeong et al, 2018;Jiang et al, 2016;Jones et al, 2019;Kuswardhani and Soejitno, 2011;Liu et al, 2015;Marquis-Gravel et al, 2014;Sun et al, 2015;Velagapudi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Dr. Hare and colleagues performed a meta‐analysis of arrhythmia end points that showed that non‐skeletal myoblast transendocardial cell therapy was associated with a significantly lower risk of sudden cardiac death or resuscitated sudden cardiac arrest, compared to control, with no proarrhythmic effects. 9 , 10 …”
Section: Cardiologymentioning
confidence: 99%